Cervical Myelopathy Due to Multilevel Ossification of the Posterior Longitudinal Ligament: A Case Report of Surgical Management With Laminoplasty - Alfred Sutrisno Sim; Herlina Uinarni; Edwin Destra (Jurnal Ners, 2026)
Ossification of the posterior longitudinal ligament (OPLL) is a degenerative spinal condition characterized by ectopic bone formation along the posterior aspect of the vertebral bodies, most commonly affecting the cervical region. This process leads to gradual spinal canal narrowing and may result in cervical myelopathy due to chronic spinal cord compression. A 52-year-old male presented with severe bilateral arm pain, progressive upper extremity weakness, and paresthesia following minor trauma. Neurological examination revealed upper limb motor deficits and positive pathological reflexes. Cervical MRI showed multilevel OPLL from C3 to C6 with significant spinal cord compression and intramedullary hyperintensity. The patient underwent cervical laminoplasty to decompress the spinal cord while preserving vertebral stability. Postoperative follow-up demonstrated substantial neurological recovery, improvement in motor function, resolution of paresthesia, and stable implant positioning. Laminoplasty is a reliable surgical option for managing cervical myelopathy in multilevel OPLL, offering effective decompression and preservation of spinal alignment and motion.